Palaeoflora Europaea: Notulae Systematicae ad Palaeofloram Europaeam spectantes I. New names of fossil magnoliophytes of the European Tertiary. I. Miscellaneous families - Doweld, Alexander B. (Phytotaxa, 2018)
The Palaeoflora Europaea Project required new names to be proposed and validated for 28 fossil taxa referable to 16 miscellaneous angiosperm families of the European Tertiary. Aniba caucasica nom. nov. is proposed instead of Aniba longifolia Kolakovsky & Schakryl (fossil) non Aniba longifolia Schwacke & Mez (extant). Ocotea undulatoides nom. nov. is proposed to replace the later homonym Ocotea undulata (Weyland & Kilpper) Uzunova & Stojanova (fossil) non Ocotea undulata (Meisner) Mez (extant), Ocotea alaris nom. nov. is proposed to replace the later homonym Ocotea alata van der Werff (extant) non Ocotea alata Givulescu (fossil). Clerodendrum sarmatiacum nom. nov. instead of Clerodendrum ovalifolium Baikovskaja (fossil) non C. ovalifolium Gray and C. ovalifolium (Jussieu) Bakhuizen (extant); Persea vanderwerffii nom. nov. instead of Persea fluviatilis van der Werff (extant) non P. fluviatilis Mai (fossil); Euphorbia pontiana nom. nov. in place of Euphorbia cylindrica Negru (fossil) non Euphorbia cylindrica Marloth ex A.C.White, R.A.Dyer & B.Sloane (extant); Malus antiqua nom. nov. instead of Malus pulcherrima Givulescu (fossil) non M. pulcherrima (Ascherson & Graebner) Boynton (extant); Meliosma antiqua nom. nov. instead of Meliosma reticulata (Reid & Reid) M.Chandler (fossil) non M. reticulata Merrill (extant); Nyssa givulescui nom. nov. instead of Nyssa maxima Givulescu, Petrescu & Barbu (fossil) non Nyssa maxima Weber (fossil). Pistacia acuminata Reid & Reid (fossil fruits) is replaced by a new name Pistacia pliolentiscus nom. nov., because of the earlier homonym P. acuminata Boissier & Buhse (extant); Pistacia miolentiscus nom. nov. is proposed to replace the later homonym Pistacia lentiscoides Andreánszky & Cziffery (fossil leaves) non Pistacia lentiscoides Unger (fossil leaves); Sterculia maoana nom. nov. instead of Sterculia cinnamomifolia Tsai & Mao (extant) non S. cinnamomifolia Engelhardt (fossil) and Sterculia acerina nom. nov. instead of Sterculia crassinervia (Ettingshausen) Prochaìzka & Bůžek (fossil) non S. crassinervia Miquel (extant); Ranunculus eoreptans nom. nov. in place of Ranunculus pusillus P.I. Dorofeev (fossil) non R. pusillus Poiret, R. pusillus Ledebour and R. pusillus Pomel (extant); Rhododendron maii nom. nov. is proposed instead of Rhododendron germanicum Mai & Walther (fossil) non Rhododendron germanicum Hoppe (extant). Viburnum pliolantana nom. nov. is proposed to replace the later homonym Viburnum lantanoides P.I. Dorofeev (fossil) non Viburnum lantanoides Michaux and Viburnum lantanoides Miquel (extant). Zanthoxylum affine Pilar (fossil leaves) is replaced by a new name Zanthoxylum pilari nom. nov., because of the earlier homonym Z. affine Kunth (extant); Zanthoxylum tethyca nom. nov. is proposed to replace the later homonym Z. rugosum (Chandler) Palamarev (fossil fruits) non Z. rugosum Saint-Hilaire & Tulasne (extant) and Z. rugosum Negru (fossil fruits). Sambucus sarmatiaca sp. nov. and Photinia sarmatiaca sp. nov. are validated instead of the previously invalidly published Baikovskaja’s fossil taxa lacking holotype designation when published. Lycopus europleistocenicus sp. nov. is validated instead of the invalidly published Lycopus intermedius Dorofeev (lacking holotype designation when published) and renamed because of the earlier homonym Lycopus intermedius Haussknecht (extant). Hibiscus sarmatiacus sp. nov. is validated instead of the invalid Hibiscus splendens Baikovskaja (lacking holotype designation when published) and renamed because of the earlier homonym Hibiscus splendens Graham (extant). Ligustrum miovulgare sp. nov. is proposed to replace invalid Ligustrum vulgare var. fossilis (lacking holotype designation when published). New combinations are validated: Cornus caroli comb. nov. (since formerly used generic designation Cynoxylon is nomenclaturally superfluous), Mahonia sphenophylla comb. nov. (to replace nomenclaturally superfluous Mahonia aspera), Toxicodendron melaenum comb. nov. (to replace invalid Toxicodendron herthae). New additional combinations are made: Aniba aniboides comb. nov.; Damburneya euxina comb. nov.; Exbucklandia germanica comb. nov.; Ocotea pithyusa comb. nov., Ocotea pontica comb. nov. Furthermore Juglans melaena is neotypified for the first time.